RELAPSING AFTER TREATMENT: EXPLORING THE EXPERIENCES OF CHEMICALLY ADDICTED ADOLESCENTS - van der Westhuizen, Marichen van der Westhuizen; de Jager, Marianna (Social Work/Maatskaplike Werk, 2009)
Relapsing after treatment for chemical addiction is common, predictable and preventable, and forms part of the addictive cycle (Buddy, 2003:1; Goodwin, 2000:91-93). Against the background of an increase in the demands for treatment of adolescent chemical addiction, as well as the persistently high relapse rate, the significant impact of chemical addiction on the development and well-being of chemically addicted adolescents needs to be considered by the social work profession, in order to plan effective intervention strategies. The purpose of this research study was to explore and describe the experiences of chemically addicted adolescents who had relapsed after in-patient treatment. Subsequently, the researcher aimed to make recommendations for social workers, in order to prevent relapse